Teknik Mother Berbantuan Channel Youtube untuk Meningkatkan Kemampuan Siswa Menulis Konjungsi Kausalitas - Nyamat, Nyamat (Jurnal Didaktika Pendidikan Dasar, 2021)
It is hoped that this research on learning the Mother technique assisted by YouTube channels is expected to be able to improve the skills of writing causality conjunctions in explanatory text and response texts of students of Sekolah Menengah Pertama Negeri 3 Pati, Central Java. The term Mother refers to two things, the first means mother while the second one from the acronym Model, Observation (observation), Write, Generate, Evaluate, and Revise. This research is a learning development research with the ADDIE model according to Dick and Carey (1996) including Analysis (analyzing student needs in writing causality conjunctions), Design (designing teaching materials using Mother's technique and validating teaching materials). Develop (development, namely testing the use of teaching materials), Implement (applying the Mother technique), and Evaluate (revising the writing of the causality conjunction of students' texts in the class which is the subject of research). The subjects of this study were two classes, namely class VIII A consisting of 32 students and class IX J totaling 27 students, so the overall subject of this study was 59 students. The results of this study showed 93% completed in groups and 92% completed individually.